1996
DOI: 10.1126/science.271.5257.1876
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the Cystic Fibrosis Transmembrane Conductance Regulator to Conduct ATP

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride ion channel regulated by protein kinase A and adenosine triphosphate (ATP). Loss of CFTR-mediated chloride ion conductance from the apical plasma membrane of epithelial cells is a primary physiological lesion in cystic fibrosis. CFTR has also been suggested to function an an ATP channel, although the size of the ATP anion is much larger than the estimated size of the CFTR pore. ATP was not conducted through CFTR in intact organs, pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(107 citation statements)
references
References 8 publications
4
101
2
Order By: Relevance
“…Regarding CFTR, this channel was initially suggested as an important ATP release channel. According to recent literature, however, it seems that CFTR in itself is not the ATP release channel but, instead, this transporter is involved in regulatory mechanisms leading to ATP release through other exit pathways (17)(18)(19)(20)(21). Our previous data has, however, left limited, if any, room for CFTR in the HlyA-induced hemolysis as we found similar HlyA-induced lysis in erythrocytes isolated from CFTR wild type and knock-out mice (26).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Regarding CFTR, this channel was initially suggested as an important ATP release channel. According to recent literature, however, it seems that CFTR in itself is not the ATP release channel but, instead, this transporter is involved in regulatory mechanisms leading to ATP release through other exit pathways (17)(18)(19)(20)(21). Our previous data has, however, left limited, if any, room for CFTR in the HlyA-induced hemolysis as we found similar HlyA-induced lysis in erythrocytes isolated from CFTR wild type and knock-out mice (26).…”
Section: Discussionmentioning
confidence: 41%
“…CFTR has been suggested to be necessary for ATP release upon mechanical deformation (10) as well as low O 2 and prostacyclin stimulation (16). It is, however, now recognized that CFTR is more likely to regulate other channels and not being directly involved in ATP release itself (17)(18)(19)(20)(21). In line with this, a recent study showed that CFTR is involved in ATP release induced by both low O 2 and prostacyclin stimulation but the exit pathway appeared to be pannexin 1 in the case of low O 2 tension (16) and VDAC for prostacyclinmediated ATP release (14).…”
mentioning
confidence: 99%
“…However, a significant number of studies failed to detect differences in extracellular ATP in normal and CFTR-deficient epithelial tissues [78][79][80]. It was also shown that swelling-induced ATP release was independent from CFTR [32,46,81].…”
Section: The Link To Cftrmentioning
confidence: 99%
“…The multidrug resistance (MDR)-1 protein, the CF transmembrane conductance regulator (CFTR) Cl − channel, and the mitochondrial voltage-dependent anion channel-1 (VDAC-1) were initially proposed as ATP release pathways or facilitators of ATP release in various cell types, but the involvement of these proteins in an ATP release function could not be corroborated by a number of studies [90][91][92][93][94][95][96]; for a critical review on these proposed pathways, see [8,97]. More recently, two classes of plasma membrane channels have been associated with an ATP conductive activity: (1) Cl − channels such as maxi anion channels, volume-regulated ion channels, and tweety; and (2) pore forming connexins, pannexins, and P2X7 receptors.…”
Section: Conductive Release Of Nucleotidesmentioning
confidence: 99%